Competence, Motivation, and Technology as Determinants of Employee Productivity: Systematic Literature Review (SLR) - Hedi Saepudin, Tubagus; Tussoleha Rony, Zahara; Ali, Hapzi (Dinasti International Journal of Management Science, 2024)
The purpose of this paper is to provide a comprehensive and detailed insight into the role of competence, motivation, and technology in determining employee productivity, as well as how organizations can effectively manage these three factors to achieve greater success and competitiveness. The research method used in this scientific article is a structured literature review. Relevant scientific articles are selected, identified, and evaluated during the literature review process. The determination of the study scope was carried out using the PICO framework (population, problem, intervention, comparison), which provides a score to establish the study limitations. A collection of relevant scientific articles is selected, excavated, and reviewed during a literature review. Using the PICO framework (population/problem, intervention, comparison), the scope of the study is determined by the score. The results of the paper provide valuable insights for human resource management practitioners and other stakeholders in managing and improving employee productivity in various types of organizations. Recommendations for practitioners include developing strategies to increase employee engagement, encouraging more flexible work practices such as teleworking, as well as strengthening motivational practices such as training and development, performance-based rewards, and knowledge sharing.